The health consequence of rising housing prices in China - Yuanwei Xu; Feicheng Wang (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
China has experienced a rapid boom in real estate prices in the last few decades, leading toa substantial increase in living costs and heavy financial burdens on households. Usingan instrumental variable approach, this paper exploits spatial and temporal variation inhousing price appreciation linked to individual-level health data in China from 2000 to 2011.We find robust evidence that increases in housing prices significantly raise the probability ofresidents having chronic diseases. This negative health impact is more pronounced amongindividuals from low-income families, households that purchased rather than inheritedor was allocated the home, and those who migrated from rural to urban areas. We alsofind evidence that marriage market competition exacerbates these negative health effects,particularly for males and parents with young adult sons. Further empirical results suggestthat housing price appreciation induces negative health consequences through increasedwork intensity, higher mental stress, and reduced sleep time. This paper provides a novelexplanation to the increased prevalence of chronic diseases in China.
Keywords: G51; I10; I12; R21; R31; 330; Housing Prices; Chronic Diseases; Health; Marriage Competition; China